An Unusual Case of Homicide by Impalement With a Battering Ram. (June 2019) - Franceschetto, Lisa; Carlini, Luigi; Lancia, Massimo; Bacci, Mauro
Abstract : Abstract: Impalement injuries occur when a large foreign body traverses or penetrates a body cavity or extremity. Nowadays, impalement injuries are uncommon and are usually a consequence of a fall onto a blunt object or a road accident. The authors report a case of a woman found dead in her apartment, seemingly killed by a firearm injury to the abdomen. However, after the autopsy was carried out, it became clear that the injuries had the features of an impalement. After the inquiry, the murder weapon was identified as a battering ram, used by the robbers to break into the house of the woman. This is the first case ever described in literature where a battering ram has been used to impale someone. This case emphasizes the importance of an accurate description of injuries, also with photographs, in order to achieve effective recognition of the wound patterns as they may correspond to specific and unusual weapons.